2003
DOI: 10.1002/syn.10305
|View full text |Cite
|
Sign up to set email alerts
|

Detailed distribution of neuropeptide FF receptors (NPFF1 and NPFF2) in the rat, mouse, octodon, rabbit, guinea pig, and marmoset monkey brains: A comparative autoradiographic study

Abstract: The distribution of neuropeptide FF receptors (NPFF(1) and NPFF(2)) was analyzed throughout the central nervous system of rodents (rat, mouse, Octodon degus, and guinea pig), rabbit, and marmoset monkey brains, representing three orders of mammals. Quantitative in vitro receptor autoradiography with [(125)I]EYF ([(125)I]EYWSLAAPQRF-NH(2)) and [(125)I]YVP ([(125)I]YVPNLPQRF-NH(2)) as specific radioligands for NPFF(2) and NPFF(1) receptors, respectively, was used. The NPFF(2) receptor is predominantly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 38 publications
4
57
1
Order By: Relevance
“…Some of these receptors display a good affinity for NPFF and are most likely involved in pain processing (37). In addition to the NPFF2R receptor subtype that is expressed in the dorsal horn of spinal cord in rodents (38), these receptors may also be activated after local intrathecal injection of a high concentration of NPFF, thus mediating spinal analgesic activity of this peptide. Our results of systemic administration of RF9 on opioid-induced hyperalgesia clearly define NPFF and its receptors as a bona fide antiopioid system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these receptors display a good affinity for NPFF and are most likely involved in pain processing (37). In addition to the NPFF2R receptor subtype that is expressed in the dorsal horn of spinal cord in rodents (38), these receptors may also be activated after local intrathecal injection of a high concentration of NPFF, thus mediating spinal analgesic activity of this peptide. Our results of systemic administration of RF9 on opioid-induced hyperalgesia clearly define NPFF and its receptors as a bona fide antiopioid system.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of NPFF1R and NPFF2R in several mammalian species (3,38,39) indicates that NPFF2R is localized to pain-processing regions, whereas NPFF1R would most likely participate in neuroendocrine function. A notable exception is human spinal cord, where NPFF1R expression has been observed while NPFF2R is present in the rodent, rabbit, and monkey (3,38,39). This exception suggests that in humans NPFF1R could play the same role in pain processing as does NPFF2R in other mammals.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that NPFF might synaptically regulate the activity of both VIP and, to a lesser degree, VP neurons within the rat SCh. This suggestion is supported by the data from in situ hybridization analysis (Liu et al, 2001) and binding studies (Gouarderes et al, 2004), which demonstrate the presence of specific receptors for NPFF in the rat SCh.…”
Section: Distribution Of Npff In the Rat Forebrainmentioning
confidence: 71%
“…In the vicinity of the NPFF fibers within the PNZ, numerous axosomatic synapses on GABAergic neurons have been identified at the electron microscopic level (Jhamandas et al, 1989). Although in situ hybridization (Liu et al, 2001) and receptor binding studies (Gouarderes et al, 2004) in the rat SO did not reveal expression of NPFF receptors NPFF1 and NPFF2, these studies did not specifically examine the PNZ region, which is where we identified dense NPFF fiber networks. Collectively, these data suggest that magnocellular VP neurons in the SO might be regulated indirectly by NPFF via GABAergic neurons in the PNZ.…”
Section: Distribution Of Npff In the Rat Forebrainmentioning
confidence: 86%
“…In line with its role in nociception, NPFF and NPFF2 are expressed in dorsal horn of the spinal cord (Panula et al 1996, Vilim et al 1999, Gouarderes et al 2002. It is important to point out that pronounced inter-species and inter-strain differences have been reported for the localisation of NPFF and its receptors (Boersma et al 1993, Gouarderes et al 2002, 2004b.…”
Section: Npff Familymentioning
confidence: 98%